G429(P) A 13 year old with fussy-eating induced blindness. (7th April 2014) - Ali, SR; Hamilton, R; Callaghan, M; Brown, A; Gibson, L
Abstract : Aim: To highlight a rare cause of blindness in developed countries, its investigation and management. Methods: A 13 year old boy was referred by his GP to the local DGH with a few months history of progressively 'fuzzy' vision, particularly at night. Aside from a history of 'fussy eating', his past medical history was unremarkable. Results: On preliminary assessment, he was systemically well, interacting appropriately and clinical examination was normal. His height and weight were on the 50 th centile for age. On ophthalmologic examination, he was found to have reduced visual acuity in the left eye with no perception of light. He had normal vision in the right eye. An MRI brain showed normal appearances of the optic nerves and chiasm. Electrodiagnostic testing was carried out and an electroretinogram (ERG) demonstrated a complete absence of rod function but nearly normal cone function. This pattern was in-keeping with that seen in vitamin A deficiency. Blood tests showed an extremely low level of vitamin A of less than 0.3 (normal 0.9–2.5 μmol/l). Serum calcium was low at 2.14 (normal 2.20–2.70 mmol/l) and vitamin B12 was also low at 176.8 (normal 190–900 pmol/l). Other routine bloods were normal. The dietary history was re-explored. The patient had an extreme selective eating pattern, consuming only crisps, chips, custard and diluting juice since the age of two. He was commenced on vitamin A supplementation and is showing improvement in his degree of visual loss. Ongoing care issues include improving nutritional status with dietetic and psychology input and repeat ophthalmology and electrodiagnostic testing to monitor progress. Conclusions: Blindness secondary to vitamin A deficiency is most common in developing countries 1 . However, sporadic cases can occur in developed countries due to nutritional insufficiency secondary to food faddism in otherwise healthy children. The condition has a variable course, permanent visual damage is possible in cases of prolonged or severe visual loss 2 . Rod function appears to recover most quickly and completely and central cones, if affected (as in this case), have slower recovery 3 . This case highlights the importance of checking for visual problems in fussy eaters and those at risk of nutritional deficiencies, thereby ensuring that appropriate management is undertaken to prevent permanent visual loss. References: Kello AB, Gilbert C. Causes of severe visual impairment and blindness in children in schools for the blind in Ethiopia. Br J Opthalmol 2003;87:526-30. McAbee GN, et al . Permanent visual loss due to dietary vitamin A deficiency in an autistic adolescent. J Child Neurol 2009;24:1288-9. Carter-Dawson L, et al . Structural and biochemical changes in vitamin A deficient rat retinas. Invest Opthalmol Vis Sci 1979;18:437-446.